PENGARUH SELF-CONCEPT, SELF-ESTEEM, SELF-EFFICACY, DAN TEKNOLOGI INFORMASI TERHADAP KINERJA MAHASISWA (STUDI PADA MAHASISWA STIE INDONESIA BANKING SCHOOL ANGKATAN 2020-2023) - Muharom , Fadhil; Pracoyo , Antyo; Nelmida , Nelmida; Paulina, Paulina (Ibs Press, 2024)
This research aims to examine “The Influence of Self-Concept, Self-Esteem, Self-Efficacy, and Information Technology on Student Performance (Study of STIE Indonesia Banking School Students Batchs 2020-2023)”. The independent variables in this research are Self-Concept, Self-Esteem, Self-Efficacy, and information technology. Meanwhile, the dependent variable in this research is student performance. Hypothesis testing in this research uses the PLS or Partial Least Square method. The data collection technique uses a google form application questionnaire to collect respondent information. The sample in this research was 209 STIE Indonesia Banking School students. The analysis results show that Self-Concept has a positive and significant effect on student performance, Self-Esteem has a positive and significant effect on student performance, Self-Efficacy has no effect on student performance, and information technology has a negative and significant effect on student performance.